Indian Intransigence in South Asian Region Under Modi Era and Complexities for Pakistan (Journal of Politics and International Studies, 2024)
In the mid of 20th century, the world has seen the emergence of two independent states, Pakistan and India, in the wave of decolonization. However, since their inception, both the nations have been arch-rivals to each other, ever seen in the history of human civilization. It would not be hyperbolic to say that India sees the existence of Pakistan as an obstruction to its treacherous national interest. Moreover, the Indian government, having the 2nd largest population in the world, wants to dominate in the entire region as well as in international politics.  India has always been striving to become a regional hegemon. For that matter, the Indian government has launched a drive of rapid modernization of military equipment. So that it can influence its immediate neighborhood under the might of its strategic design. Thus, the growing belligerent and aggressive strategic design of India has been disturbing the equation of balance of power in South Asia.